ETHNOBOTANY SAGO (Metroxylon sago Rottb) in JAILOLO LOCAL COMMUNITY, WEST HALMAHERA REGENCY, INDONESIA - Hasan, Said; Tolangara, Abdulrasyid; Ahmad, Hasna; Sahil, Jailan; Suparman, Suparman (Jurnal Pendidikan Matematika dan IPA, 2024)
Sago plants have long played an important role in people's lives, particularly in eastern Indonesia"”such as in Papua, Maluku, and North Maluku. The objective of this study was to investigate how the local community in Jailolo District, West Halmahera Regency, utilizes sago plants in line with their traditional wisdom. The research method employed is exploratory-descriptive, which is valuable for depicting the characteristics of a phenomenon. This research was conducted in Jailolo District, West Halmahera Regency, and lasted for 3 months, from January to February 2023. The methodology involved direct observation and collected information from Sahu ethnic by interviews with the snowball sampling method. Additionally, documentation of the various forms of sago plant utilization was undertaken, encompassing sago stems, bark, fronds, sago leaf stalks, sago leaves, and sago flour. The data collected in this study were analyzed using qualitative descriptive analysis and presented in a narrative format. The results revealed that a majority of the people in Jailolo District, West Halmahera Regency, utilized sago plants to fulfill their daily needs, using them as an alternative food source to substitute rice. Sago plants are utilized in various forms, primarily in the form of sago flour, which is used to create a range of processed foods such as bagea, sago macarons, popeda, boko-boko, sago plates, sago sugar, and sinyole. Additionally, sago leaves are utilized for roofing houses, while sago fronds are used for ceilings, walls, and crafts such as paludi (Saloi). Sago stems are used to extract starch (flour), while the bark is utilized as firewood.